Epoxy mortar timber beam upgrading. (3rd July 2017) - de Carvalho, Sander Samuel; Panzera, Túlio Hallak; Christoforo, André Luis; Fiorelli, Juliano; Lahr, Francisco Antonio Rocco; Freire, Rodrigo Teixeira Santos
ABSTRACT: The physical and mechanical properties of brown-pigmented particulate composites based on epoxy polymer reinforced with quartz particles were assessed experimentally. The best setup condition was chosen to repair Maçaranduba and Cedrinho timber species. A full factorial design was conducted to evaluate the effect of the quartz particle (0, 40, 50, 60 wt-%) and pigment (0, 0.02 wt-%) inclusions on the density, apparent porosity, compressive modulus and strength. The composite made with 50 wt-% of quartz particles and 0.02 wt-% of pigment revealed promising characteristics for restoration works, being used to repair the upper (under compression) side of timber beams evaluated under four-point bending tests. The timber beams were evaluated in pristine, with defect and in repaired conditions. Repaired Cedrinho timber achieved similar mechanical behaviour when compared with pristine conditions. In contrast, the repair procedure was not successful in restoring the load capacity of damaged Maçaranduba timber beams.